PENGARUH RETURN ON INVESMENT (ROI), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS) DAN ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM - Ela Widasari; Vera Faridoh (Universitas La Tansa Mashiro, 2017)
Return is the goal of investors to invest in the capital market. One form of return obtained by investors in investing in the capital market is stock returns in the form of capital gains. Increasing stock prices will increase the company's stock return. The purpose of this study is to determine whether there is an effect of Return on Investment (ROI), Return On Equity (ROE), Earning Per Share (EPS) and Economic Value Added (EVA) on stock returns. This study uses a quantitative method with a descriptive approach. The type of data in this study is secondary data and determine the sample using the purposive sampling method. The sample in this study were automotive sector companies and components listed on the Indonesia Stock Exchange (IDX) for the period 2011 - 2015. Testing the hypothesis used is by testing the significance of individual parameters (statistical test t), simultaneous significance test (F statistical test) and coefficient of determination. The results of the study state that only Earning Per Share (EPS) has a positive and significant effect on stock returns, while the Return on Investment (ROI), Return On Equity (ROE), and Economic Value Added (EVA) do not have a positive and significant effect on stock returns the automotive sector and component companies listed on the Indonesia Stock Exchange (IDX) for the period 2011 – 2015.